Researching Parenting in Pandemic Times: Tips and Traps from an Italian Experience - Monaco, Salvatore (Italian Sociological Review, 2022)
Italian sociological studies exploring parenting in challenging circumstances from material, cultural, or relational perspectives are still few. Therefore, in 2019, the national interest project Constructions of Parenting on Insecure Grounds (CoPInG) was launched with the aim of analyzing the construction of parenthood and practices of “doing family” in uncertain circumstances. It is a qualitative study, which, using the grounded theory approach, aims to give voice and visibility to some of the most vulnerable parent groups (for example, parents living in poverty and precarious economic conditions; parents with forced migration backgrounds; gay, lesbian, bisexual, and trans parents; and parents facing violent conﬂicts). The advent of COVID-19 upset the initial research design of the CoPInG project, making it even more difficult to recruit Italian parents and carry out the scheduled interviews. In this scenario, the research group identified and adopted alternative solutions to continue the project regardless. This paper examines the impact of digital technology on research that was originally designed to be offline, focusing in particular both on the possibilities offered by new communication channels to intercept vulnerable subjects and on strategies to be implemented to conduct the foreseen interviews. Thus, the global aim of this work is to introduce a series of critical reflections on digital innovations in social research on parenting in Italy [...]